Positive electrode material, positive electrode sheet, secondary battery, and electric device
Patent Information
- Application Number
- CN202380009733.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-03-27
AI Technical Summary
[0003]三元正极材料NCM体系能量密度高、成本低、寿命长,但安全性能、生产工艺的可控性不足
[0012] In any embodiment of the first aspect, 0.062 < w'(Co)/w'(Ni) ≤ 0.410, optionally w'(Co)/w'(Ni) is 0.062 to 0.158, further optionally w'(Co)/w'(Ni) is 0.083 to 0.136. Ternary cathode material generations with different Ni contents have great performance differences; under the same generation of ternary cathode materials with the same Ni content, limiting the Co content within the above range can more prominently reduce costs and improve low-temperature performance, while also avoiding the problems of deteriorated electrical conductivity of the material and degraded rate performance caused by excessively low Co content.
Smart Images

Figure CN116848663B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a positive electrode material, a positive electrode sheet, a secondary battery, and an electrical device. Background Technology
[0002] Since the commercialization of lithium-ion batteries, their advantages such as high energy density, high battery voltage, long cycle life, and no memory effect have led to their rapid adoption as energy storage devices in various aspects of life, and have also attracted widespread interest from experts and researchers.
[0003] Ternary cathode materials (NCM systems) offer high energy density, low cost, and long lifespan, but suffer from insufficient safety performance and controllability in manufacturing processes. Compared to ternary cathode materials, phosphate cathode materials offer advantages such as low cost, long cycle life, and stable charge-discharge cycles at high temperatures, making them a more ideal cathode material for large-scale lithium-ion battery applications. However, lithium iron phosphate materials exhibit low conductivity, poor rate performance, and unsatisfactory low-temperature performance (especially below -30°C). Summary of the Invention
[0004] This application provides a positive electrode material, a positive electrode sheet, a secondary battery, and an electrical device to improve the low-temperature power and low-temperature capacity retention of the battery.
[0005] In a first aspect, this application provides a cathode material, including a phosphate-based cathode material and a ternary cathode material, wherein the cathode material satisfies the following relationship 1:
[0006] Relationship 1: 0.032 <w(Co) / (w(Ni)+w(Mn)+w(A))≤0.075
[0007] Wherein, A is the doping element in the phosphate-based cathode material, w(Co) is the mass percentage of Co in the cathode material, w(Ni) is the mass percentage of Ni in the cathode material, w(Mn) is the mass percentage of Mn in the cathode material, and w(A) is the mass percentage of A in the cathode material.
[0008] The cathode material of this application controls the Co content in the cathode material to satisfy the above relationship 1, thereby reducing the electron conductivity, increasing the impedance, increasing the battery cycle temperature rise, and thus improving the battery's low-temperature power and low-temperature capacity retention rate; in addition, the reduction of Co content is also beneficial to the cost of raw materials.
[0009] In any embodiment of the first aspect, 1.55<w(Co)<3.25, optionally 1.8<w(Co)<2.9, further optionally 1.85<w(Co)<2.85; and / or 17.55<w(Ni)<29.55, optionally 19.2<w(Ni)<29.2, further optionally 19.9<w(Ni)<26.5; and / or 16.55<w(Mn)<21.55, optionally 18.2<w(Mn)<21.1, further optionally 18.4<w(Mn)<20.85; and / or 1.05<w(A)<6.55, optionally 2.2<w(A)<6.5, further optionally 2.35<w(A)<5.85. Control of the content of each of the above elements, especially control of Co content, can simultaneously guarantee the low-temperature performance, energy density, cycling performance and cost benefit of the battery.
[0010] In any embodiment of the first aspect, w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.035 to 0.065, optionally 0.045 to 0.060, which further improves the low-temperature performance of the battery.
[0011] In any embodiment of the first aspect, the mass percentage of Ni element in the ternary cathode material satisfies 20% <w'(Ni) ≤ 55%, optionally 25% ≤ w'(Ni) ≤ 50%, or 30% ≤ w'(Ni) ≤ 45%, or 30% ≤ w'(Ni) ≤ 40%. When the Ni element content in the ternary cathode material is within the above range, the ternary cathode material can have favorable energy density and rate cycling performance.
[0012] In any embodiment of the first aspect, 0.062 < w'(Co) / w'(Ni) ≤ 0.410, optionally w'(Co) / w'(Ni) is 0.062 to 0.158, further optionally w'(Co) / w'(Ni) is 0.083 to 0.136. Ternary cathode material generations with different Ni contents have great performance differences; under the same generation of ternary cathode materials with the same Ni content, limiting the Co content within the above range can more prominently reduce costs and improve low-temperature performance, while also avoiding the problems of deteriorated electrical conductivity of the material and degraded rate performance caused by excessively low Co content.
[0013] In any embodiment of the first aspect, 0.08 < w(A) / w(Ni) ≤ 0.41, optionally w(A) / w(Ni) is 0.10 to 0.30, further optionally 0.12 to 0.28. Further limiting the ratio of phosphate cathode material to ternary cathode material by using the above relational expression can better exert the superior performances of both materials.
[0014] In any embodiment of the first aspect, the phosphate-based cathode material has the chemical formula Li 1+x Mn 1-y A y P 1- z E z O4, where x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, and Ge, and may be selected from one or more elements from the group consisting of Fe, Ti, V, and Mg, and E includes one or more elements from the group consisting of B, Si, N, S, F, Cl, and Br, and optionally, E is an element selected from the group consisting of B, Si, N, and S. Doping phosphates with elements A and E helps to improve the structural stability of phosphate cathode materials and the rate performance of secondary batteries containing them.
[0015] In any embodiment of the first aspect, the chemical formula of the phosphate-based cathode material is Li a A1 x Mn 1-y A2 y P 1- z D z O 4-n G n The phosphate-based cathode material is electrically neutral. A1 comprises one or more elements from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W; A2 comprises one or more elements from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; D comprises one or more elements from the group consisting of B (boron), S, Si, and N; G comprises one or more elements from the group consisting of S, F, Cl, and Br; a is selected from the range of 0.9 to 1.1; x is selected from the range of 0.001 to 0.1; y is selected from the range of 0.001 to 0.5; z is selected from the range of 0.001 to 0.1; n is selected from the range of 0.001 to 0.1. Furthermore, the phosphate-based cathode material is electrically neutral. By simultaneously doping the aforementioned specific elements in specific amounts at the four positions, the rate performance, cycle performance, and / or high-temperature stability of the phosphate-based cathode material can be significantly improved.
[0016] In any embodiment of the first aspect, the phosphate cathode material may optionally further have a core-shell structure, the shell layer of the core-shell structure is a functional coating layer, and the functional coating layer may optionally be one or more layers of pyrophosphate, phosphate and carbon. The above functional coating layer can effectively inhibit the dissolution of transition metals and reduce side reactions on the surface of the phosphate cathode material.
[0017] In any embodiment of the first aspect, the ternary cathode material conforms to the chemical formula Li a Ni b Co c M1 d M2 e O f R g or Li with a coating layer disposed on the surface a Ni b Co c M1 d M2 e O f R g , wherein 0.75≤a≤1.2, 0.38<b<0.85, 0.03<c<0.15, 0<d<1, 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3, M1 comprises one or both of Mn and Al, optionally the molar ratio of Al to Mn is 0 to 1:4, M2 comprises one or more selected from the group consisting of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W and Nb, and R comprises one or more selected from the group consisting of N, F, S and Cl.
[0018] A second aspect of the present application provides a cathode pole piece, comprising a current collector and a cathode film layer, wherein the cathode film layer comprises the cathode material according to any embodiment of the first aspect. The cathode pole piece having the above cathode material of the present application can achieve improvement of the low-temperature power and low-temperature capacity retention rate of a battery, and reduce raw material costs.
[0019] In any embodiment of the second aspect, the coating areal density of the above cathode film layer is 15.50 to 20.78 mg / cm 2 , and / or the compacted density of the cathode active material is 2.4 to 3.40 g / cm 3 . The cathode pole piece having the above coating areal density or compacted density has a high capacity value, is also favorable for the manufacturing process, and has an improvement effect on the power performance of the cell.
[0020] A third aspect of the present application provides a secondary battery, which comprises a cathode pole piece, a separator, an electrolyte and an anode pole piece, wherein the cathode pole piece is any one of the above cathode pole pieces. The low-temperature power and low-temperature capacity retention rate of the secondary battery are effectively improved.
[0021] A fourth aspect of this application provides an electrical device including a secondary battery, which includes any of the secondary batteries described in the third aspect above. This improves the power performance and charging capability of the electrical device at low temperatures. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of a secondary battery according to one embodiment of this application.
[0024] Figure 2 yes Figure 1 An exploded view of a secondary battery according to one embodiment of this application is shown.
[0025] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0026] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0027] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0028] Figure 6 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.
[0029] The accompanying drawings are not drawn to scale.
[0030] Explanation of reference numerals in the attached figures:
[0031] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Secondary battery; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation
[0032] The embodiments of this application will be described in further detail below with reference to the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to illustrate the principles of this application by way of example, but should not be used to limit the scope of this application, that is, this application is not limited to the described embodiments.
[0033] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the positive electrode material, positive electrode sheet, negative electrode sheet, secondary battery, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0034] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0035] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0036] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0037] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0038] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0039] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0040] [Rechargeable Battery]
[0041] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged after being discharged to activate the active materials and continue to be used.
[0042] Typically, a secondary battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During charging and discharging, active ions (such as lithium ions) repeatedly insert and extract between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing active ions to pass through. The electrolyte, also positioned between the positive and negative electrodes, mainly serves to conduct active ions.
[0043] [Cathode Material]
[0044] One embodiment of this application provides a cathode material, which includes phosphate-based cathode materials and ternary cathode materials, and the cathode materials satisfy the following relationship 1:
[0045] Relationship 1: 0.032 <w(Co) / (w(Ni)+w(Mn)+w(A))≤0.075
[0046] Wherein, A is the doped metal element in the phosphate-based cathode material, w(Co) is the mass percentage of Co in the cathode material, w(Ni) is the mass percentage of Ni in the cathode material, w(Mn) is the mass percentage of Mn in the cathode material, and w(A) is the mass percentage of A in the cathode material.
[0047] The content of each metal element in the cathode material can be tested using the following method: Using a 1+1 ratio of aqua regia, the mixed cathode powder sample is digested by microwave digestion at 200℃ and high pressure. The main elements of the mixed cathode are then tested by inductively coupled plasma atomic emission spectrometry (ICP-AES) using an ICAP-7400 instrument.
[0048] The cathode material of this application controls the Co content in the cathode material to satisfy the above relationship 1, so that the Co content of the cathode material is relatively low, thereby reducing the electron conductivity, increasing the impedance, increasing the battery cycle temperature rise, and thus improving the battery low-temperature power and low-temperature capacity retention rate; in addition, the reduction of Co content is also beneficial to the raw material cost benefit.
[0049] In some implementations, 1.55 <w(Co)<3.25,16.20<w(Ni)<29.55,16.55<w(Mn)<21.55,1.05<w(A)<6.55。
[0050] The above w(Co) can be selected from the above range, including but not limited to 1.55, 165, 1.75, 1.80, 1.85, 1.95, 2.0, 2.02, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.0, 3.05, 3.10, 3.15, 3.20 or 3.25.
[0051] The above-mentioned w(Ni) can be selected from the above range, including but not limited to 16.20, 16.50, 17.00, 17.50, 18.00, 18.50, 18.70, 19.0, 19.50, 19.60, 18.80, 20.00, 22.30, 20.50, 21.00, 21.10, 21.20, 21.50, 21.60, 22.00, 22.50, 23.00, 23.50, 24.00, 24.50, 25.00, 25.20, 25.50, 26.00, 26.50, 27.00, 27.50, 28.00, 28.50, 29.00, and 29.50.
[0052] The above w(Mn) can be arbitrarily selected within the above range, including but not limited to 17.55, 18.00, 18.25, 18.40, 18.50, 19.00, 19.50, 20.00, 20.10, 20.15, 20.50, 21.00, 21.10, 21.20, 21.30, 21.40, 21.50, 21.55.
[0053] The above w(A) can be arbitrarily selected within the above range, including but not limited to 1.05, 1.10, 1.50, 2.00, 2.10, 2.30, 2.40, 2.70, 2.80, 2.90, 3.00, 3.20, 3.40, 3.50, 3.70, 3.80, 4.00, 4.10, 4.30, 4.50, 4.70, 4.90, 5.00, 5.20, 5.40, 5.60, 5.80, 6.00, 6.30, 6.50.
[0054] If the Co content is too low, the positive electrode sheet will have poor electrical conductivity, which easily leads to deterioration of the rate performance and cycle performance of the battery. When the Co content is higher than a certain level, it will cause a decrease in the relative contents of Ni / Mn, resulting in loss of the energy density and plateau voltage of the battery and increased raw material cost. In some embodiments, 1.8 < w(Co) < 2.9, optionally 1.85 < w(Co) < 2.85; and / or 19.2 < w(Ni) < 29.2, optionally 19.9 < w(Ni) < 26.5; and / or 18.2 < w(Mn) < 21.1, optionally 18.4 < w(Mn) < 20.85; and / or 2.2 < w(A) < 6.5, optionally 2.35 < w(A) < 5.85. The control of the content of each of the above elements, especially the control of Co content, can simultaneously ensure the low-temperature performance, energy density, low-temperature cycle performance and cost benefit of the battery.
[0055] In some embodiments, the value of w(Co) / (w(Ni)+w(Mn)+w(A)) includes but is not limited to 0.032, 0.033, 0.035, 0.036, 0.037, 0.038, 0.040, 0.042, 0.045, 0.048, 0.050, 0.054, 0.059, 0.060, 0.063, 0.065, 0.070, 0.075. In some embodiments, w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.035 to 0.065, optionally 0.045 to 0.060, so as to further improve the low-temperature performance of the battery.
[0056] Ternary cathode material generations with different Ni contents have great performance differences. In some embodiments, the mass percentage of Ni element in the ternary cathode material is 20%<w'(Ni)≤55%, which can optionally be 25%≤w'(Ni)≤50%, or 30%≤w'(Ni)≤45%, or 30%≤w'(Ni)≤40%. When the Ni element content in the ternary cathode material is within the above range, the ternary cathode material can have good energy density and rate cycling performance. Ternary cathode materials with the above w'(Ni) generally belong to ternary cathode materials in which Ni accounts for 50-60% of the total molar amount of Ni, Co and Mn, or ternary cathode materials in which Ni accounts for 60-70% of the total molar amount of Ni, Co and Mn.
[0057] In some embodiments, 0.062<w'(Co) / w'(Ni)≤0.410, and said w'(Co) / w'(Ni) includes but is not limited to 0.062, 0.065, 0.066, 0.070, 0.074, 0.078, 0.080, 0.082, 0.083, 0.085, 0.087, 0.090, 0.093, 0.095, 0.100, 0.110, 0.120, 0.125, 0.128, 0.130, 0.135, 0.140, 0.145, 0.155, 0.160, 0.167, 0.2, 0.3, 0.4. Optionally, w'(Co) / w'(Ni) is 0.062 to 0.158, and further optionally, w'(Co) / w'(Ni) is 0.083 to 0.136. Under the same generation of ternary cathode materials with the same Ni content, limiting the Co content within the above range can more prominently reduce costs and improve low-temperature performance, while also avoiding the problems of deteriorated electrical conductivity and poor rate performance of the material caused by excessively low Co content.
[0058] Since ternary cathode materials have higher capacity energy density and voltage platform compared with phosphate cathode materials, while phosphate cathode materials have better cycling stability and cost advantages compared with ternary cathode materials, in some embodiments, 0.08<w(A) / w(Ni)≤0.41, and said w(A) / w(Ni) includes but is not limited to 0.080, 0.085, 0.09, 0.093, 0.095, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.2, 0.22, 0.25, 0.26, 0.28, 0.3, 0.4. Optionally, w(A) / w(Ni) is 0.10 to 0.30, and further optionally 0.12 to 0.28. Further limiting the ratio of phosphate cathode material to ternary cathode material by using the above relational expression can better exert the advantageous properties of both.
[0059] The phosphate-based cathode material used in this application can be a commonly used undoped phosphate-based cathode material, a doped phosphate-based cathode material, or a coated phosphate-based cathode material. In some embodiments, the phosphate-based cathode material has the chemical formula Li. 1+x Mn 1-y A y P 1-z E z O4, where x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, and Ge, and may be selected from one or more elements from the group consisting of Fe, Ti, V, and Mg, and E includes one or more elements from the group consisting of B, Si, N, S, F, Cl, and Br, and optionally, E is an element selected from the group consisting of B, Si, N, and S. Doping phosphates with elements A and E helps to improve the structural stability of phosphate cathode materials and the rate performance of secondary batteries containing them.
[0060] In some embodiments, the chemical formula of the above-mentioned phosphate-based cathode material is Li a A1 x Mn 1-y A2 y P 1-z D z O 4-n G nWherein, A1 includes one or more elements from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W; A2 includes one or more elements from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; D includes one or more elements from the group consisting of B (boron), S, Si, and N; G includes one or more elements from the group consisting of S, F, Cl, and Br; a is selected from the range of 0.9 to 1.1, for example, 0.97, 0.977, 0.984, 0.988, 0.99, 0.991, 0.992, 0.993, 0.994, 0.995, 0.996, 0.997, 0.998, 1.01; and x is selected from 0.001 to 0. The range of 1 is, for example, 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1; y is selected from the range of 0.001 to 0.5, for example, 0.001, 0.005, 0.02, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.34, 0.345, 0.349, 0.35, 0.4, 0.5; z is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, 0.1; n is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, 0.1; and the phosphate-based cathode material is electrically neutral. A1, A2, D, and G are the elements doped at the Li, Mn, P, and O sites of the compound LiMnPO4, respectively. Not wanting to be confined to theory, it is now believed that the performance improvement of phosphate-based cathode materials is related to reducing the lattice change rate and decreasing surface activity during lithium insertion / extraction. Reducing the lattice change rate can decrease the difference in lattice constants between the two phases at the grain boundary, reduce interfacial stress, and enhance Li... +The transport capacity at the interface enhances the rate performance of the positive electrode active material. However, high surface activity easily leads to severe interfacial side reactions, exacerbating gas generation, electrolyte consumption, and interface damage, thus affecting the battery's cycle performance. The aforementioned phosphate-based positive electrode materials reduce the lattice change rate through Li and Mn site doping. Mn site doping also effectively reduces surface activity, thereby suppressing Mn dissolution and interfacial side reactions between the positive electrode active material and the electrolyte. P-site doping accelerates the change rate of the Mn-O bond length, lowering the small polaron migration barrier and thus improving electronic conductivity. O-site doping has a good effect on reducing interfacial side reactions. P-site and O-site doping also affects the Mn dissolution and kinetic properties of antisite defects. Therefore, doping reduces the concentration of antisite defects in the material, improves the material's kinetic properties, and can also change the particle morphology, thereby increasing the compaction density. The applicant unexpectedly discovered that by simultaneously doping specific elements at specific amounts at the Li, Mn, P, and O sites of the compound LiMnPO4, significantly improved rate performance can be obtained, while significantly reducing the dissolution of Mn and Mn-site dopants, resulting in significantly improved cycle performance and / or high-temperature stability, and the material's density and compaction density can also be increased. The combination of A1 and A2 mentioned above constitutes the metal doping element in the phosphate-based cathode material defined above.
[0061] In some embodiments, the phosphate-based cathode material may further have a core-shell structure, where the shell layer is a functional coating layer, which may be one or more layers of pyrophosphate, phosphate, or carbon. Since the migration barrier of transition metals in pyrophosphate is high (>1 eV), the dissolution of transition metals can be effectively suppressed. Phosphate has excellent lithium-ion conductivity and can reduce surface lithium impurities. The carbon layer can effectively improve the conductivity and desolvation capability of LiMnPO4, and also acts as a "barrier" to further hinder the migration of manganese ions into the electrolyte and reduce the corrosion of the active material by the electrolyte. Simultaneously, the carbon layer in the mixture can also optimize the conductive network around the ternary cathode material, improving the mixing uniformity of the phosphate-based cathode material and the ternary cathode material.
[0062] The ternary cathode material used in this application can be a commonly used ternary cathode material. In some embodiments, the ternary cathode material conforms to the chemical formula Li. a Ni b Co c M1 d M2 e O f R g Or Li with a coating layer on its surface a Ni b Co c M1 d M2e O f R g , wherein 0.75≤a≤1.2, 0.38<b<0.85, 0.03<c<0.15, 0<d<1, 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3, M1 comprises one or both of Mn and Al, optionally the molar ratio of Al to Mn is 0 to 1:4, M2 comprises one or more selected from the group consisting of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W and Nb, and R comprises one or more selected from the group consisting of N, F, S and Cl.
[0063] Both the phosphate positive electrode active materials and ternary positive electrode materials used in the present application can be existing materials in the prior art or prepared by known methods, for example, a series of lithium manganese iron phosphate positive electrode materials produced by Shenzhen Dynanonic Co., Ltd. (referred to as Dynanonic in the examples); a series of ternary positive electrode materials produced by Ningbo Ronbay New Energy Technology Co., Ltd. (referred to as Ronbay Technology in the examples).
[0064] [Positive electrode plate]
[0065] A positive electrode plate generally comprises a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode material according to any one of the above embodiments of the present application. The positive electrode plate having the positive electrode material of the present application can improve the low-temperature power and low-temperature capacity retention rate of a battery and reduce raw material costs.
[0066] By way of example, the positive electrode current collector has two opposite surfaces in its own thickness direction, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector.
[0067] In some embodiments, the coating areal density of the above positive electrode film layer is 15.50 to 20.78 mg / cm 2 , and / or the compacted density of the positive electrode active material is 2.4 to 3.40 g / cm 3 . The positive electrode plate having the above coating areal density or compacted density has a high capacity value, is also favorable for the processing technology, and also has an improvement effect on the power performance of the battery cell.
[0068] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0069] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0070] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0071] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive electrode material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0072] [Negative electrode plate]
[0073] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0074] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0075] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0076] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0077] In some embodiments, the negative electrode film layer may optionally include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0078] In some embodiments, the negative electrode film may optionally include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0079] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0080] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0081] [Electrolytes]
[0082] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0083] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0084] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0085] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0086] In some embodiments, the electrolyte may optionally include additives. As examples, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0087] [Isolation membrane]
[0088] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0089] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0090] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0091] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0092] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0093] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 This is an example of a square-structured secondary battery 5.
[0094] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 can be placed over the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 52 using a winding or stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The secondary battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.
[0095] In some implementations, the secondary batteries can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.
[0096] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.
[0097] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.
[0098] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0099] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0100] In addition, this application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0101] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements.
[0102] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0103] [Example]
[0104] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0105] The source of cathode materials, including phosphate-based cathode materials such as LiMn 0.6 Fe 0.4 PO4 was purchased from DY-3 type phosphate from Defang Nano, and the ternary cathode material was purchased from S760 series ternary materials from Rongbai Technology. The remaining cathode materials were prepared using the following methods.
[0106] Preparation Example 1
[0107] 1) Preparation of positive electrode active materials
[0108] Preparation of doped manganese oxalate: 1.3 mol of MnSO4·H2O and 0.7 mol of FeSO4·H2O were thoroughly mixed in a mixer for 6 hours. The mixture was transferred to a reaction vessel, and 10 L of deionized water and 2 mol of oxalic acid dihydrate (calculated as oxalic acid) were added. The reaction vessel was heated to 80 °C and stirred at 600 rpm for 6 hours until the reaction was terminated (no more bubbles were generated), yielding an Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120 °C and then ground to obtain a median particle size Dv. 50 The particles are Fe-doped manganese oxalate particles with a diameter of approximately 100 nm.
[0109] Preparation of doped lithium manganese phosphate: 1 mol of the above-mentioned manganese oxalate particles, 0.4985 mol of lithium carbonate, 0.0005 mol of Al2(SO4)3, an 85% phosphoric acid aqueous solution containing 0.999 mol of phosphoric acid, 0.001 mol of H4SiO4, 0.0005 mol of NH4HCl2, and 0.005 mol of sucrose were added to 20 L of deionized water. The mixture was transferred to a sand mill and thoroughly ground and stirred for 10 hours to obtain a slurry. The slurry was then transferred to a spray drying equipment for spray drying and granulation. The drying temperature was set at 250℃, and the powder was dried for 4 hours to obtain granules. Under a protective atmosphere of nitrogen (90 vol%) + hydrogen (10 vol%), the powder was sintered at 700℃ for 10 hours to obtain carbon-coated Li. 0.997 Al 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 Cl 0.001 .
[0110] Preparation Example 2
[0111] (1) Preparation of co-doped lithium manganese phosphate core
[0112] Preparation of Fe-co-doped manganese oxalate: 689.5 g of manganese carbonate (calculated as MnCO3, the same below) and 463.4 g of ferrous carbonate (calculated as FeCO3, the same below) were thoroughly mixed in a mixer for 6 hours. The mixture was transferred to a reaction vessel, and 5 liters of deionized water and 1260.6 g of oxalic acid dihydrate (calculated as C2H2O4·2H2O, the same below) were added. The reaction vessel was heated to 80°C and stirred at 600 rpm for 6 hours until the reaction was terminated (no bubbles were generated), resulting in a Fe-co-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain Fe and S-co-doped manganese oxalate dihydrate particles with a median particle size Dv50 of 100 nm.
[0113] Preparation of Fe and S co-doped lithium manganese phosphate: 1793.4 g of manganese oxalate dihydrate particles (calculated as Li₂CO₃), 369.0 g of lithium carbonate (calculated as Li₂CO₃), 1.6 g of 60% dilute sulfuric acid (calculated as 60% H₂SO₄), and 1148.9 g of ammonium dihydrogen phosphate (calculated as NH₄H₂PO₄) obtained in the previous step were added to 20 L of deionized water. The mixture was stirred for 10 hours to ensure homogeneity, resulting in a slurry. The slurry was then transferred to a spray dryer for spray drying and granulation. The drying temperature was set at 250 °C, and the drying time was 4 hours to obtain powder. Under a nitrogen (90 vol%) + hydrogen (10 vol%) protective atmosphere, the powder was sintered at 700 °C for 4 hours to obtain 1572.1 g of Fe and S co-doped lithium manganese phosphate (Li₂CO₃). 0.999 Mn 0.60 Fe 0.40 P 0.99 9S 0.001 O4.
[0114] The methods for determining the content of each element in the material are as follows:
[0115] Take approximately 0.4g of dry positive electrode sheet / powder or approximately 1g of moist positive electrode sheet / powder (both accurate to 0.0001g) in a 25ml beaker, add 2ml-5ml of nitric acid, let stand overnight, then place on a hot plate and heat at approximately 100℃ (using a voltage regulator to adjust the input voltage for temperature control) until the positive electrode sheet / powder is digested. Add 0.5ml of perchloric acid and heat at approximately 140℃ to digest until all white fumes are emitted. The residue should be white; otherwise, repeat the digestion with nitric acid and perchloric acid. Finally, dissolve and extract with 7% (volume percentage of acid, the same below) hydrochloric acid. Adjust the volume to an appropriate level according to the content of the element to be tested, and then start the test on the ICP-OES instrument.
[0116] The test results and corresponding calculations are recorded in Table 1.
[0117] In Table 1, the ternary mass content represents the mass content of the ternary cathode material in the overall ternary cathode material and phosphate cathode material.
[0118]
[0119]
[0120] 1. Square aluminum-cased battery:
[0121] Square aluminum-cased batteries were prepared using the positive electrode materials listed in Table 1 as the positive electrode active material. The preparation method is as follows.
[0122] ① Preparation of positive electrode sheet:
[0123] Positive electrode active material, polyvinylidene fluoride (PVDF), and conductive carbon were added to a certain amount of N-methylpyrrolidone (NMP). The mass ratio of active material: binder: conductive agent was 98:1:1. The mixture was stirred in a drying room to prepare a uniform slurry with a viscosity controlled at 3000–10000 mPa·s. The slurry was then coated onto aluminum foil, with a coating density of 18.77 mg / cm². 2 After drying and cold pressing, the final positive electrode sheet is produced.
[0124] ② Preparation of negative electrode sheet:
[0125] Graphite, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon are added to a certain amount of deionized water. The mass ratio of graphite:sodium carboxymethyl cellulose:styrene-butadiene rubber:conductive agent is 90:2:3:5. The mixture is stirred to form a uniform slurry with a viscosity controlled at 3000-10000 mPa·s. The slurry is then coated onto copper foil and dried and cold-pressed to form a negative electrode sheet.
[0126] ③ Fabrication of square aluminum-cased batteries:
[0127] The prepared and slit positive electrode sheet, negative electrode sheet, and separator (polyethylene (PE) porous polymer film) are wound together, followed by ultrasonic welding of the positive and negative electrode tabs. The positive electrode uses aluminum tabs, and the negative electrode uses copper tabs, with the positive and negative electrode tabs located on the same side of the cell. The cell with the tabs welded is then installed into an aluminum shell of appropriate size for soft connection and top cover welding. The cell is vacuum dried at 175℃ for 24 hours, followed by electrolyte injection (the electrolyte is 1 mol / L LiPF6 / (ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC)) (volume ratio 1:1:1) + 5 wt.% fluoroethylene carbonate (FEC)), followed by standing, formation, aging, venting, secondary sealing, and capacity testing to obtain the prepared square aluminum shell battery.
[0128] 2. Low-temperature performance testing: -20℃ test current power / -7℃ operating condition test
[0129] -7℃ Operating condition test: The square aluminum-cased battery prepared above was subjected to CLTC national standard operating condition test at -7℃ (range of 2.1V-4.4V) and 25℃ (range of 2.5V-4.4V). The discharge capacity C0 and C1 at room temperature of 25℃ and -7℃ were recorded respectively. The low temperature capacity retention rate was calculated by C1 / C0.
[0130] -20℃ Test Current Power Test: At -20℃, within the range of 2.1V-4.4V, first charge the cell with a constant current of 0.33C, then charge it to 4.4V with a constant voltage of 0.05C, and then discharge it to 10% SOC with a constant current of 0.33C. Apply any current for 10s of discharge and record the voltage value after 10s of discharge. When the current is at its maximum and the voltage is still >2.1V after 10s, record the corresponding discharge currents I0 and U0 at that moment. The test current power is I0*U0.
[0131] 3. 25℃ Cyclic Performance Test:
[0132] The battery prepared above was charged to 4.4V at 0.5C0 under a constant temperature environment of 25℃ and a voltage range of 2.5 to 4.4V. Then, it was charged at 4.4V under constant voltage until the current was ≤0.05C0. After standing for 5 minutes, it was discharged to 2.5V at 1C0. The capacity was recorded as Cn (n=1,2,3……). The above operation was repeated. After 500 charge-discharge cycles, the capacity retention rate was calculated according to the ratio of C500 / C3. The corresponding capacity retention rate was used as the evaluation index of cycle capability.
[0133] 4. Rate performance test at 25℃:
[0134] At 25°C, the above-mentioned battery cell is charged at a constant current of 0.33C to 4.4V, charged at a constant voltage of 0.05C, and then discharged at a constant current of 0.33C to 2.5V. This charge-discharge cycle is repeated 3 times, and the third discharge capacity is taken as C1. At 25°C, the above-mentioned battery cell is charged at a constant current of 0.33C to 4.4V, charged at a constant voltage of 0.05C, and then discharged at a constant current of 2C to 2.5V. This charge-discharge cycle is repeated 3 times, and the third discharge capacity is taken as C2. C2 / C1 can characterize the discharge rate capability of the battery cell at 2C.
[0135] The results are recorded in Table 2.
[0136] Table 2
[0137]
[0138]
[0139] The test results show that the Co content in the ternary NCM material and the proportion of NCM in the mixed cathode both affect the low-temperature power and low-temperature capacity retention of the battery. Examples 1-6 adjusted the mass percentage of Co relative to Ni+Mn+A in the limiting electrode, and Examples 7-10 adjusted the range of the Co mass percentage in the electrode. Comparing the data from Examples 1 to 10, it was found that controlling the Co content in the cathode material to a relatively low level reduces electron conductivity, increases impedance, and increases the battery's cycle temperature rise, thereby improving the battery's low-temperature power and low-temperature capacity retention. However, the low Co content in Examples 1 and 2 results in poor conductivity of the cathode, easily leading to deterioration in battery rate performance and cycle performance. Conversely, when the Co content is too high in Example 6, it causes a decrease in the relative Ni / Mn content, resulting in losses in battery energy density and plateau voltage, and increased raw material costs.
[0140] Examples 11-15 adjust the range of Ni mass percentage in the electrode, Examples 16-19 adjust the range of Mn mass percentage, Examples 20-26 adjust the range of A mass percentage, and Examples 41-46 adjust the range of A / Ni ratio in the electrode. The adjustment of the content of each element, especially the Co content in Examples 8 and 9, can simultaneously ensure the battery's low-temperature performance, energy density, cycle performance, and cost-effectiveness.
[0141] The performance of ternary cathode materials with different Ni contents varies greatly. Examples 27-35 adjust the mass percentage of Ni in the ternary material NCM. Among them, the Ni element in the ternary cathode material in Example 31 enables the cathode material to have good low-temperature performance while also having high energy density and rate cycling performance.
[0142] Examples 36-38 adjust the relative levels of Co / Ni in NCM. Under the same generation of ternary cathode materials with the same Ni content, limiting the Co content within the above range can more significantly reduce costs and improve low-temperature performance. At the same time, it avoids the problem that the conductivity of the material deteriorates and the rate performance deteriorates due to too low Co content.
[0143] Comparative Examples 1 and 2 show that when the LMAP content in the electrode is too high, the battery energy density gain will deteriorate; Comparative Examples 3 and 4 show that when the Co content in the NCM of the electrode is too high, the battery cycle rate performance is improved and the internal resistance is reduced, but the advantages of the battery at low temperature power and low temperature capacity retention will be deteriorated, and the cost will also increase.
[0144] Although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A cathode material, comprising phosphate-based cathode materials and ternary cathode materials, in, The phosphate-based cathode material is LiMn. 0.6 Fe 0.4 PO4, the ternary cathode material conforms to the chemical formula LiNi 0.61 Co 0.08 Mn 0.31 O2 and w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.060; Alternatively, the phosphate-based cathode material may be LiMn. 0.6 Fe 0.4 PO4, the ternary cathode material conforms to the chemical formula LiNi 0.53 Co 0.07 Mn 0.40 O2 and w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.065; Alternatively, the phosphate-based cathode material may be LiMn. 0.6 Fe 0.4 PO4, the ternary cathode material conforms to the chemical formula LiNi 0.62 Co 0.08 Mn 0.30 O2 and w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.059; Alternatively, the phosphate-based cathode material may be LiMn. 0.6 Fe 0.4 PO4, the ternary cathode material conforms to the chemical formula LiNi 0.612 Co 0.078 Mn 0.31 O2 and w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.059; Alternatively, the phosphate-based cathode material may be LiMn. 0.65 Fe 0.35 PO4, the ternary cathode material conforms to the chemical formula LiNi 0.61 Co 0.08 Mn 0.31 O2 and w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.061; Alternatively, the phosphate-based cathode material may be LiMn. 0.6 Fe 0.4 PO4, the ternary cathode material conforms to the chemical formula LiNi 0.60 Co 0.06 Mn 0.34 O2 and w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.048; Or the phosphate-based cathode material is Li 0.997 Al 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 Cl 0.001 The ternary cathode material conforms to the chemical formula LiNi 0.61 Co 0.08 Mn 0.31 O2 and w(Co) / (w(Ni)+w(Mn)+w(A)) is 0.060, In each of the above w(Co) / (w(Ni)+w(Mn)+w(A)), A is at least one of Fe and Al in the phosphate cathode material, w(Co) is the mass percentage of Co in the cathode material, w(Ni) is the mass percentage of Ni in the cathode material, w(Mn) is the mass percentage of Mn in the cathode material, and w(A) is the mass percentage of A in the cathode material.
2. A positive electrode sheet, comprising a current collector and a positive electrode film layer, wherein, The positive electrode film layer comprises the positive electrode material as described in claim 1.
3. A secondary battery, said secondary battery comprising a positive electrode, a separator, an electrolyte, and a negative electrode, wherein, The positive electrode is the positive electrode as described in claim 2.
4. An electrical device comprising a secondary battery, wherein, The secondary battery includes the secondary battery as described in claim 3.
Citation Information
Patent Citations
Cobalt-coated positive electrode material and preparation method thereof, positive plate and lithium ion battery
CN114094068A
Cathode materials for lithium ion batteries
US20210083289A1